A Step toward Understanding Information Processing in Plants. Explaining the Complexity of Life Thanks to Plants Physiology (2015)
This article argues that the complexity of life can be largely understood and explained by a somewhat “minor” field in biology, namely botany. The complexity of the plant’s cell as well as the modularity of the organization of plants serves as conditions to the explanation of life on earth. Plants process information in a quite different way than animals, and the plant’s anatomy and physiology are to be taken as the rationale for life on Earth.